Ignition and reaction mechanisms of thermal explosion reaction in the Ni-Ti-C system under air and Ar - Yang, Y.F.; Wang, H.Y.; Wang, J.G.; Zhao, R.Y.; Jiang, Q.C. (Journal of materials research, 2009)
The ignition and reaction mechanisms of the thermal explosion reaction in the Ni-Ti-C system under air and Ar conditions were investigated. The reaction for the formation of TiC can be initiated at a low temperature under air. The ignition temperature under air is much lower than that under Ar. Under Ar, both the ignition and reaction mechanisms consist of dissolution, reaction, and precipitation. Under air, the ignition mechanism is confirmed to be the chemical oven mechanism, and the reaction mechanism is dissolution, reaction, and precipitation. The mechanism of gas transport plays a much more minor role in the ignition and reaction processes under air.